Decelerated Greenland Ice Sheet Melt Driven by Positive Summer North Atlantic Oscillation. Issue 14 (27th July 2019) - Ruan, Ruomei; Chen, Xianyao; Zhao, Jinping; Perrie, William; Mottram, Ruth; Zhang, Minghong; Diao, Yina; Du, Ling; Wu, Lixin
Abstract: The abrupt deceleration of accelerated Greenland Ice Sheet (GrIS) melting since 2013, after a period of acceleration previously noted, is studied here. It is shown that the deceleration of GrIS melting since 2013 is due to the reduction in short‐wave solar radiation in the presence of increasing total cloud cover, which is driven by a more persistent positive summer North Atlantic Oscillation on the decadal time scale. By presenting the coherence with the temperature variability at the weather stations in Greenland, which have century‐long records, we deduce that the acceleration of GrIS melting during the early 2000s and the subsequent deceleration since 2013 will reoccur frequently on decadal time scales, with the amplitude nearly half of the multidecadal warming trend of the GrIS melt. It can reduce the mass loss from the GrIS on short to medium time scales but is unlikely to halt mass loss related to climate change in the future. This finding highlights the importance of internal climate variability on the mass budget of the GrIS and therefore on predictions of future global sea level change and may help to assist planning for associated social and economic consequences. Plain Language Summary: The Greenland Ice Sheet (GrIS) mass change and its contribution to the global sea level variability is a topic that naturally piques our curiosity. Since the satellite first captured the Greenland‐wide ice sheet mass variability in 2002, the GrIS experienced accelerated melting, leading to global sea level acceleration. The long‐term GrIS melting depends on climate change such as greenhouse warming. However, recently, this acceleration is slowed down due to the summer North Atlantic Oscillation phase changing to positive. We use century‐long surface temperature records as index to estimate the contribution of this slowdown phenomenon and find that the amplitude of this internal variability is nearly half of the multidecadal warming trend of the GrIS; therefore, this cycle can slow down but cannot stop the loss of the Greenland Ice Sheet mass at present and in the near future. This finding highlights the role of the internal variability of the GrIS on predictions of future global sea level change and the associated social and economic consequences. Key Points: Greenland Ice Sheet exhibits decelerated melt since 2013 The deceleration is due to increased cloud during positive summer NAO The accelerated and decelerated GrIS melt will reoccur on decadal time scale